3D CFD simulations: effect of operation parameters on the deposition of photocatalytic TiO2 nanoparticles by MOCVD - Othman, Siti Hajar; Abdul Rashid, Suraya; Mohd Ghazi, Tinia Idaty; Abdullah, Norhafizah (Wiley-VCH Verlag GmbH & Co. KGaA, 2015)
A 3-dimensional (3D) computational fluid dynamics (CFD) simulation study on the effect of temperature and carrier-gas flow rate on the deposition of photocatalytic titanium dioxide (TiO2) nanoparticles by metal-organic (MO)CVD is presented. The model predicts the temperature, velocity, mass fraction of reactants and products, kinetic rate of reaction, and surface deposition rate profiles. Increasing temperature and reducing carrier gas flow rate increases the deposition rate and hence the amount of nanoparticles produced. Unlike carrier-gas flow rate, temperature is significant in determining the rate of surface deposition. Simulation results are validated by experiments whenever possible due to limited data. Decent agreement between experiment and simulation supports the reliability of the simulation.